Rekonstruksi Politik Luar Negeri Indonesia di Tengah Dinamika Lingkungan Strategis Indo-Pasifik Abad ke-21 - Ian Montratama (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
Indo-Pacific region is the most dynamic region in the 21st century with the economic growth that exceeds the rest of the world. Increased prosperity of countries in the region is accompanied by an increase in the defense budget that leads to arms race. The phenomenon is due to the existence of a conflict of interests among countries in the region in various forms. Border dispute is the most sensitive issue that can escalated into armed conflict. Such prominent problem is the border dispute over the territorial waters between some ASEAN countries with China in the South China Sea (SCS). SCS dispute involving China, Vietnam, Philippines, Malaysia, Brunei, and Taiwan. This article presents an in-depth review of the foreign policy of the Indonesian government should play in the Global Maritime Nexus vision in dealing with the dynamics of the strategic environment in the Indo-Pacific region in the 21st century.